Aerodynamic analysis of the aerospaceplane HyPlane in supersonic rarefied flow. (June 2016) - Zuppardi, Gennaro; Savino, Raffaele; Russo, Gennaro; Spano' Cuomo, Luca; Petrosino, Eliano
Abstract: HyPlane is the Italian aerospaceplane proposal targeting, at the same time, both the space tourism and point-to-point intercontinental hypersonic flights. Unlike other aerospaceplane projects, relying on boosters or mother airplanes that bring the vehicle to high altitude, HyPlane will take off and land horizontally from common runways. According to the current project, HyPlane will fly sub-orbital trajectories under high-supersonic/low-hypersonic continuum flow regimes. It can go beyond the von Karman line at 100 km altitude for a short time, then starting the descending leg of the trajectory. Its aerodynamic behavior up to 70 km have already been studied and the results published in previous works. In the present paper some aspects of the aerodynamic behavior of HyPlane have been analyzed at 80, 90 and 100 km. Computer tests, calculating the aerodynamic parameters, have been carried out by a Direct Simulation Monte Carlo code. The effects of the Knudsen, Mach and Reynolds numbers have been evaluated in clean configuration. The effects of the aerodynamic surfaces on the rolling, pitching and yawing moments, and therefore on the capability to control attitude, have been analyzed at 100 km altitude. The aerodynamic behavior has been compared also with that of another aerospaceplane at 100 km both in clean and flapped configuration.